Potential of CXCR4/CXCL12 Chemokine Axis in Cancer Drug Delivery - Wang, Yan (Curr Pharmacol Rep, 2016)
This review discusses the potential of CXCR4 chemokine receptor in the design of anticancer and antimetastatic drug delivery systems. The role of CXCR4 in cancer progression and metastasis is discussed in the context of the development of several types of drug delivery strategies. Overview of drug delivery systems targeted to cancers that overexpress CXCR4 is provided, together with the main types of CXCR4-binding ligands used in targeting applications. Drug delivery applications that take advantage of CXCR4 inhibition to achieve enhanced anticancer and antimetastatic activity of combination treatments are also discussed.